2022
DOI: 10.1126/sciadv.abk2376
|View full text |Cite
|
Sign up to set email alerts
|

Mitolysosome exocytosis, a mitophagy-independent mitochondrial quality control in flunarizine-induced parkinsonism-like symptoms

Abstract: Mitochondrial quality control plays an important role in maintaining mitochondrial homeostasis and function. Disruption of mitochondrial quality control degrades brain function. We found that flunarizine (FNZ), a drug whose chronic use causes parkinsonism, led to a parkinsonism-like motor dysfunction in mice. FNZ induced mitochondrial dysfunction and decreased mitochondrial mass specifically in the brain. FNZ decreased mitochondrial content in both neurons and astrocytes, without affecting the number of nigral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…3g, the images of the mitophagy assay showed that the colocalization of green-marked mitochondria and red-marked lysosomes in the MLPers group was higher than that in the other treatment groups. Notably, Rot caused the aggregation of mitochondria (punctate uorescent dots instead of strips), mitochondrial mass sharply decreased, and the punctate uorescent dots labeled by MitoTracker Green in the MLPers group were colocalized with lysosomes 35 . Together, these data indicated that Parkin protein overexpression in MLPers group enhanced mitophagy during mitochondrial transfer.…”
Section: Resultsmentioning
confidence: 99%
“…3g, the images of the mitophagy assay showed that the colocalization of green-marked mitochondria and red-marked lysosomes in the MLPers group was higher than that in the other treatment groups. Notably, Rot caused the aggregation of mitochondria (punctate uorescent dots instead of strips), mitochondrial mass sharply decreased, and the punctate uorescent dots labeled by MitoTracker Green in the MLPers group were colocalized with lysosomes 35 . Together, these data indicated that Parkin protein overexpression in MLPers group enhanced mitophagy during mitochondrial transfer.…”
Section: Resultsmentioning
confidence: 99%
“…However, several recent studies have pointed to mitochondrial stress triggering the release of mitochondrial fragments through the autophagic machinery. For instance, mitochondria in acidic lysosomes, or mitoysosomes, are released by dopaminergic neurons and astrocytes through lysosome exocytosis following Flunarizine-induced Parkinsonism(Bao, Zhou et al 2022). Similarly, cardiomyocytes release mitochondria and mitochondrial fragments in an autophagy-dependent manner during cardiac stress(Nicolás-Ávila, Lechuga-Vieco et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of ATG5 or knockout of LC3 adapters have no effect on this process, indicating a novel means by which mitochondria interact with lysosomes. 25 An OMM protein-BAX, which was identified by genome-wide CRISPR knockout screen as essential for mitochondrial entry into lysosomes, is also capable of translocation to the membranes of lysosomes, 127 BAX may mediate the direct interaction between mitochondria and lysosomes. The mitolysosome facilitates the secretion of mitochondria-containing vesicles.…”
Section: Mitolysosome Exocytosismentioning
confidence: 99%
“…Flunarizine, a drug induces mitolysosome exocytosis, treatment could induce parkinsonismlike symptoms in mice. 25 Chronic use of flunarizine often leads to parkinsonism. 165 It is tempting to extrapolate that mitolysosome exocytosis may decrease neural mitochondria and release mitochondria-containing vesicles, both of which contribute to the pathologic of PD.…”
Section: Parkinsonism and Other Neurological Diseasesmentioning
confidence: 99%